Personality and Team Identification Predict Violent Intentions Among Soccer Supporters - Lindström, Joanna (Frontiers in Sports and Active Living, 2021)
Soccer supporter violence remains a persistent global problem. The majority of research examining the psychological underpinnings of soccer supporter violence have focused primarily on the role of team identification. Relatively little research has examined the role of basic personality traits and willingness to engage in violence amongst soccer supporters. In a study amongst Swedish soccer supporters (N = 247), we examined whether honesty-humility and team identification predict violent behavioral intentions; examining if collective narcissism mediates these associations. Honesty-humility negatively predicted violent intentions, and team identification predicted violent intentions. Collective narcissism partially mediated these associations. When both Honesty-humility and team identification are accounted for though, collective narcissism did not predict violent intentions. Such findings have implications for the design of violence prevention interventions amongst soccer supporters.